Diversidade de oligoquetas na transição entre a Amazônia oriental e o cerrado - Sousa, Anny Mykaelly de (2023)
The transition between the Cerrado and the Amazon biome is located in the North and East portion of the state of Maranhão, where the two biomes cover the entire state and stand out as world hostpots due to the rich biodiversity of fauna and flora. Recent studies indicate the presence of new species of the oligochaeta group, mainly from the Belém Endemism Area, known as ecosystem engineers, a group sensitive to environmental disturbances, adaptable to anthropic activities in soil profiles and responsible for various ecosystem functions. Carrying out a descriptive work on this group is important for understanding the processes that structure and aggregate the soil, as well as for understanding life in the soil and the functioning of physical-chemical processes that affect all the diversity of macrofauna. The objective of this project was to describe the earthworm communities in the eastern Amazon and Cerrado transition, and as specific objectives to verify the occurrence of new earthworm species for the two biomes, contribute to the advancement of new research within the state and compare the diversity of earthworms using two collection methods. To carry out this research, a compilation of data on earthworms collected in the eastern Amazon was used, and the complementation of these data through new collections made in the Cerrado of eastern Maranhão. Sampling took place during the rainy season in the municipalities of Alcântara, São Luís, Itinga do Maranhão, Rosário, São José de Ribamar, Centro Novo do Maranhão, Tome Açú and Caxias, based on the TSBF method and the adaptation of the TSBF method by Decãens et al. (2016). The identification of earthworms was performed using taxonomic keys. Based on the results, it was possible to analyze the occurrence of 5,180 earthworms, which were classified into three ecological categories: epigeic, endogenous and anecic. The categories with the highest numbers of earthworms were Epigeic and Endogeic, mostly found in conserved places and close to streams, strongly influenced by long rainy periods and soil use.